Agglomeration economies, firm-level efficiency and productivity growth: empirical evidence from Indonesia - Widodo, Wahyu (Curtin University, 2013)
This thesis examines the effect of agglomeration economies on firm-level efficiency and productivity growth in Indonesian manufacturing industries. The stochastic production frontier (SPF), Färe-Primont productivity index and econometric estimation are applied. Empirical results show evidence of positive specialization effects and negative diversity effects, indicating that specialization is more favourable than diversity for stimulating firm-level efficiency and productivity growth. It confirms that inter-firm knowledge spillovers are transmitted in the regions that consist of homogeneous industries.